ANALISIS KESANTUNAN BERBAHASA WARGANET DALAM EPILOG MENSREA : STUDI KASUS KOMENTAR YOUTUBE PANDJIE PRAGIWAKSONO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is entitled "An Analysis of Netizen Politeness in the Epilogue of Mens Rea: A Case Study of Pandjie Pragiwaksono's YouTube Comments." This research is motivated by the phenomenon of low levels of digital politeness among Indonesian netizens, particularly in responding to political discourse that triggers polarization. The main problem in this study is how politeness strategies are used and negotiated in the YouTube comment section, which is characterized by the online disinhibition effect. The purpose of this study is to describe the forms of politeness strategies based on Brown & Levinson's theory. The methodology used is a qualitative approach with a descriptive qualitative design. Data in the form of netizen comments on Pandji Pragiwaksono's YouTube video "Epilogue of Mens Rea" were collected through documentation, listening, and note-taking techniques using a purposive sampling procedure. Data analysis was carried out through stages of reduction, presentation, and drawing conclusions from a pragmatic perspective. The research findings show that netizens employ four politeness strategies: bald on-record politeness for the efficiency of urgent messages, positive politeness for building solidarity, negative politeness through the use of hedges to respect the autonomy of the interlocutor, and off-record politeness through metaphors and sarcasm to avoid direct responsibility for harsh criticism. It was found that politeness in the digital space is fluid; initially cooperative interactions can transform into aggressive ones as threats to "face" increase due to ideological differences.